2021
DOI: 10.1007/s10858-021-00365-x
|View full text |Cite
|
Sign up to set email alerts
|

A COVID moonshot: assessment of ligand binding to the SARS-CoV-2 main protease by saturation transfer difference NMR spectroscopy

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the etiological cause of the coronavirus disease 2019, for which no effective antiviral therapeutics are available. The SARS-CoV-2 main protease (Mpro) is essential for viral replication and constitutes a promising therapeutic target. Many efforts aimed at deriving effective Mpro inhibitors are currently underway, including an international open-science discovery project, codenamed COVID Moonshot. As part of COVID Moonshot, we used saturation tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…61) -Fig. 1A) shows one of the highest binding affinities 62 and therefore provides a reasonable starting point for fragmentbased design of novel M pro inhibitors.…”
Section: Resultsmentioning
confidence: 96%
“…61) -Fig. 1A) shows one of the highest binding affinities 62 and therefore provides a reasonable starting point for fragmentbased design of novel M pro inhibitors.…”
Section: Resultsmentioning
confidence: 96%
“…Most of the unassigned proton amides lie in the first two β‐barrel domains or at the dimerization interface (Figure S2). Whereas previous attempts to record multidimensional NMR data on SARS‐CoV [38] and SARS‐CoV‐2 [39] 3CLp have failed, these new NMR data open the field to a large range of future studies of the dimeric 3CLp in solution and at temperature close to physiological, an important parameter when considering dynamics. To assess the potential of our experimental system, we analyzed the 3CLp spectral perturbations upon binding of either boceprevir or GC376 (Figures S3,S4).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas structural biology plays a central role in drug discovery and drug development, up to date, NMR spectroscopy has not successfully been pushed forward to study the 3CLp from coronaviruses. [ 37 , 38 , 39 ] In this work, we used solution‐state NMR spectroscopy to study the dimeric 3CLp protease of the SARS‐CoV‐2, which is one of the main targets to develop efficient antivirals to fight against the COVID‐19 pandemic. Considering the high sequence conservation between the 3CLps,[ 20 , 40 ] our data will also be valuable for others β‐coronaviruses, such as MERS‐CoV and SARS‐CoV (67 % and 98 % sequence similarity, respectively), and possibly for future emerging β‐coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the STD ratio is roughly inversely proportional to K D . [41] While the ratio is influenced by the extent of NOE magnetisation transfer from protein to ligand, dissociation rate and effective ligand concentration, these influences should be minimized across variable fragment scaffolds by only considering the strongest STD signal in the aromatic region and using presumably weakly binding, fast exchanging ligands. Six compounds ( 1 , 2 , and 5 – 8 , Table 1 ) also showed binding in WaterLOGSY experiments and were progressed to competition experiments (Figure 7 b, Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…In combination with a competing ligand or the use of different enzyme variants they can also deliver information about the binding sites of the compounds. In addition, STD ratio [41] and % displacement can be used to rank compounds by affinity. In the case of the compounds were both values could be determined ( 1 , 2 , 5 and 7 ) they showed the same trends indicating that these measures are in agreement (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%